2019
DOI: 10.1186/s13054-019-2547-x
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific differences in survival after out-of-hospital cardiac arrest: a nationwide, population-based observational study

Abstract: Background It remains unclear whether men have more favorable survival outcomes after out-of-hospital cardiac arrest (OHCA) than women. Methods We reviewed a total of 386,535 patients aged ≥ 18 years with OHCA who were included in the Japanese registry from 2013 to 2016. The study endpoints were the rates of 1-month survival and neurologically intact survival (Cerebral Performance Category Scale score = 1 or 2). Based on age, the reviewed patients were categorized into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 48 publications
0
28
1
Order By: Relevance
“…However, it is not clear whether sex differences in heart-related diseases affect the prognosis of OHCA. Multiple studies have addressed possible sex differences associated with OHCA prognosis, but the findings are inconsistent: some studies report no difference between males and females in survival after OHCA [ 7 , 11 ]; others have reported better survival for males or better survival for females [ 12 , 13 ]. A meta-analysis published in 2015 showed that the discharge survival rate of female OHCA patients was 10% higher than that of male, but the results of the latest large clinical studies show conflicting trends [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not clear whether sex differences in heart-related diseases affect the prognosis of OHCA. Multiple studies have addressed possible sex differences associated with OHCA prognosis, but the findings are inconsistent: some studies report no difference between males and females in survival after OHCA [ 7 , 11 ]; others have reported better survival for males or better survival for females [ 12 , 13 ]. A meta-analysis published in 2015 showed that the discharge survival rate of female OHCA patients was 10% higher than that of male, but the results of the latest large clinical studies show conflicting trends [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The baseline characteristics of each group are comparable. There is a slight increase in the proportion of women in the PLR group, but this was not associated with worse outcomes (22).…”
Section: Discussionmentioning
confidence: 82%
“…This could be explained by the higher prevalence of cardiovascular disease and lifestyle risk factors in men [ 21 ]. Many studies have shown that survival outcomes differ between the sexes, although the findings are somewhat contradictory [ 14 , 22 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have shown that estrogen administration may improve cardiac arrest outcomes [ 11 , 12 ]. Contrarily, some studies have reported that the OHCA survival rate among females in the reproductive age, was similar to that in males [ 13 , 14 ]. Further research is required to explain these conflicting results.…”
Section: Introductionmentioning
confidence: 95%